Peer Counselor Training to Improve Mental Health Literacy and Basic Counseling Skills among Vocational High School Students - Kusnulia Rosita; Umi Fajar Azizah; Su’ad Jauharoh (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Adolescent mental health is an important issue in school settings, particularly among vocational high school students who face academic, social, emotional, and career-related developmental demands. Peer counselor training can serve as a promotive and preventive strategy to strengthen students’ mental health literacy and basic helping skills in the school environment. This community service program aimed to empower students at SMK IT Smart Informatika Surakarta through peer counselor training focused on mental health awareness, empathetic communication, active listening, and basic counseling practice. The program was implemented through several stages, including field surveys, participant selection using open-ended questionnaires, training module preparation, material delivery, role-play practice, and evaluation. A total of 23 selected female students participated in the training facilitated by psychologists. The training was conducted on November 13–14, 2025, in the school hall. Evaluation was carried out through observation, participant responses, role-play performance, video simulation assignments, and pretest–posttest scores. The results showed that all participants were actively involved, enthusiastic, and able to complete the role-play and video simulation assignments on time. The average understanding score increased from 58.16 in the pretest to 82.40 in the posttest, indicating improved mental health literacy and understanding of peer counseling roles. Participants also demonstrated better empathetic communication, active listening, and readiness to provide initial support to peers. These findings indicate that peer counselor training is relevant for strengthening student empowerment and school-based mental health support. The program provides practical implications for schools and guidance and counseling services in developing sustainable peer support systems to promote adolescent psychological well-being.